2020
DOI: 10.1016/j.ijid.2020.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical features of 125 Hospitalized Patients with COVID-19 in Fuyang, Anhui, China

Abstract: To investigate the epidemiological and clinical features of patients with COVID-19 in Anhui province of China. Method: In this descriptive study, we obtained epidemiological, demographic, manifestations, laboratory data and radiological findings of patients confirmed by real-time RT-PCR in the NO.2 People's Hospital of Fuyang City from Jan 20 to Feb 9, 2020. Clinical outcomes were followed up to Feb 18, 2020. Results: Of 125 patients infected SARS-CoV-2, the mean age was 38.76 years (SD, 13.799) and 71(56.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
191
4
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(231 citation statements)
references
References 18 publications
16
191
4
15
Order By: Relevance
“…A total of 907 studies were retrieved through the search, of which 19, 8-26 16 from China, 1 from Korea, and 2 from the United States, included data on smoking behavior and COVID-19 disease progression (Supplementary Table S1). Seventeen studies [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26] were based on hospitalized patients and two 8,13 included both hospitalized patients and outpatients.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 907 studies were retrieved through the search, of which 19, 8-26 16 from China, 1 from Korea, and 2 from the United States, included data on smoking behavior and COVID-19 disease progression (Supplementary Table S1). Seventeen studies [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26] were based on hospitalized patients and two 8,13 included both hospitalized patients and outpatients.…”
Section: Methodsmentioning
confidence: 99%
“…The exposure group for our analysis were those who had a history of smoking (current smokers or former smokers) and unexposed group was never smokers. Nine studies 10,12,14,18,20,21,23,25,26 assessed whether the patient was a "current smoker," five studies 8,9,13,16,24 assessed whether the patient was a current or former smoker (as separate categories), and five studies 11,15,17,19,22 assessed whether the patient had a "history of smoking" (current or former).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Main symptoms are fever, cough, and fatigue, all presenting reactions of an activated immune system (Guan et al, 2020). The activation of the immune and the complement system is also observed by a variety of markers including increased values for interleukin (IL)-6 (52% of the patients), erythrocyte sedimentation rate (85%), serum ferritin (63%), and C-reactive protein (CRP) (86%) Risitano et al, 2020;Wang et al, 2020;Zhang et al, 2020c;Zhou et al, 2020a). Furthermore, recent studies that monitored and compared coagulation parameters of COVID-19 patients have suggested a tendency to procoagulant states Ji et al, 2020;Tang et al, 2020) and an increased risk of venous thromboembolism (Giannis et al, 2020), which was indicated by higher levels of fibrin/fibrinogen degradation products and fibrinogen itself, as well as lower antithrombin levels .…”
Section: Introductionmentioning
confidence: 99%